If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -24 = 4y + -63 Reorder the terms: -24 + 7y = 4y + -63 Reorder the terms: -24 + 7y = -63 + 4y Solving -24 + 7y = -63 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -24 + 7y + -4y = -63 + 4y + -4y Combine like terms: 7y + -4y = 3y -24 + 3y = -63 + 4y + -4y Combine like terms: 4y + -4y = 0 -24 + 3y = -63 + 0 -24 + 3y = -63 Add '24' to each side of the equation. -24 + 24 + 3y = -63 + 24 Combine like terms: -24 + 24 = 0 0 + 3y = -63 + 24 3y = -63 + 24 Combine like terms: -63 + 24 = -39 3y = -39 Divide each side by '3'. y = -13 Simplifying y = -13
| 4k-(6-2k)=10 | | 1/6-1/2 | | 2z+3(-4+4z)=-3 | | cu+cv+du+dv= | | 6(n+4n)= | | 5x^2-6x+28=14 | | 0.71-(.22s)=1.03-0.62s | | 10s-2=9s+6 | | (am+bm)+(an+bn)= | | 2(-5a+1)-5=-10+10a | | 1/3(x-15)+2x=16 | | 2x+234=4x | | 10a-3=-10+10a | | 10+49+-8-10= | | 3.8-4= | | x+2x-2+x+2x-2= | | x+3.8=4 | | 5(3y-9)=45 | | x+5-5=13-5 | | 9x=8x+72 | | 37+7y=85 | | 10-.2x=1 | | 2.5x+2x+.6x= | | 37+7y=86 | | (3/7)x^2+5=0 | | .02x-.16x=.7 | | 10-9=5x+10 | | 10s-5+3=9s+6 | | -4(5)-4(-8)= | | 6x+12y=4 | | k+4+l=18 | | 5(4z)-1/2z=234 |